PFKP Activation Ameliorates Foot Process Fusion in Podocytes in Diabetic Kidney Disease - Zhang, Zongwei; Liang, Wei; Luo, Qiang; Hu, Hongtu; Yang, Keju; Hu, Jijia; Chen, Zhaowei; Zhu, Jili; Feng, Jun; Zhu, Zijing; Chi, Qingjia; Ding, Guohua (Frontiers in Endocrinology, 2022)
Background: Glycolysis dysfunction is an important pathogenesis of podocyte injury in diabetic kidney disease (DKD). Foot process fusion of podocytes and increased albuminuria are markers of early DKD. Moreover, cytoskeletal remodeling has been found to be involved in the foot process fusion of podocytes. However, the connections between cytoskeletal remodeling and alterations of glycolysis in podocytes in DKD have not been clarified. Methods: mRNA sequencing of glomeruli obtained from db/db and db/m mice with albuminuria was performed to analyze the expression profiling of genes in glucose metabolism. Clotrimazole (CTZ) was used to explore the renal effects of PFKP inhibition in diabetic mice. Using Pfkp siRNA or recombinant plasmid to manipulate PFKP expression, the effects of PFKP on high glucose (HG) induced podocyte damage were assessed in vitro. The levels of fructose-1,6-bisphosphate (FBP) were measured. Targeted metabolomics was performed to observe the alterations of the metabolites in glucose metabolism after HG stimulation. Furthermore, aldolase type b (Aldob) siRNA or recombinant plasmid were applied to evaluate the influence of FBP level alteration on podocytes. FBP was directly added to podocyte culture media. Db/db mice were treated with FBP to investigate its effects on their kidney. Results: mRNA sequencing showed that glycolysis enzyme genes were altered, characterized by upregulation of upstream genes (Hk1, and Pfkp) and down-regulation of downstream genes of glycolysis (Pkm, and Ldha). Moreover, the expression of PFKP was increased in glomeruli of DKD patients. The CTZ group presented more severe renal damage. In vitro, the Pfkp siRNA group and ALDOB overexpression group showed much more induced cytoskeletal remodeling in podocytes, while overexpression of PFKP and suppression of ALDOB in vitro rescued podocytes from cytoskeletal remodeling through regulation of FBP levels and inhibition of the RhoA/ROCK1 pathway. Furthermore, targeted metabolomics showed FBP level was significantly increased in HG group compared with the control group. Exogenous FBP addition reduced podocyte cytoskeletal remodeling and renal damage of db/db mice. Conclusions: These findings provide evidence that PFKP may be a potential target for podocyte injury in DN and provide a rationale for applying podocyte glycolysis enhancing agents in patients with DKD.